Studi Kenyamanan Ergonomi Berdasarkan Dimensi Anthropometri Anak - Rahmat, Dhaifa Fatimah; Kamilah, Nurlyana; Farijwajdi, Agus; Aripin, Jaenal; Saputra, Guntur; Basri, Dian Monica Erveline (Local Engineering, 2025)
Children are our future that need to be taken cacer of. Their number one activity is studying at school. For them to bea able to dostudying effectively, school must provide architectural facilities which are able to accommodate children’s comfort as the main building user. But around, we still see so many children’s facilities, especially schools, that haven’t considered chidren’s anthropometric dimension in their design process, hence their inability to accommodate children’s comfort in doing their activities effectively. Because of those facts, the researcher decided to do research regarding ergonomic comfort based on children’s anthropometric dimension. The chosen case study is SDN Ulujami 02. The research method is descriptive quantitative, where the measuring process is described in diagrams and paragraphs. Afetr analyzing process is done, it is concluded that there are two research variables that are considered comfortable; and one research variable is quite comfortable.